2017
DOI: 10.30918/mri.53.17.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of bacterial pathogens from treated tannery wastewater

Abstract: The aim of this study was to isolate, characterize and identify the bacterial pathogens from treated tannery wastewater and also to study their multi-drug and multi-metal resistance property. Three bacterial strains of pathogen species with more antagonistic activity were identified as Pantoea sp., E. coli sp., and Lysinibacillus spp., with accession nos. KJ576899, KJ576900 and KJ576904, respectively for public domain. The antibiotic and heavy metal resistant property of isolated bacterial strains was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…The MIC of Ni was observed to be 8 mM in their study. Another study, conducted by Chowdhary et al [43], stated the MIC of Ni resistant bacterial isolate to be 24 mM, which is in agreement with our results. The results are also similar to the results of Alboghobeish et al [39], who reported the MBC of the Ni-resistant Klebsiella oxytoca species to be 24 mM.…”
Section: Discussionsupporting
confidence: 93%
“…The MIC of Ni was observed to be 8 mM in their study. Another study, conducted by Chowdhary et al [43], stated the MIC of Ni resistant bacterial isolate to be 24 mM, which is in agreement with our results. The results are also similar to the results of Alboghobeish et al [39], who reported the MBC of the Ni-resistant Klebsiella oxytoca species to be 24 mM.…”
Section: Discussionsupporting
confidence: 93%
“…However, the results were barely comparable with the toxins of ancient tanneries [ 67 ]. A similar scenario was also recognized for Indian tanneries [ 68 ].…”
Section: Discussionsupporting
confidence: 62%
“…Lysinibacillus spp. are bacterial pathogens, while Cloacibacterium are extremotolerant organisms and both have been also reported in this type of effluents (Chowdhary et al 2017, Nascimento et al 2018. Members of the Proteobacteria phylum, such as Brachymonas, Campylobacter, Halomonas, Acinetobacter and Rickettsiella showed similar sequence relative abundances (1-4 %) (Table SV).…”
Section: S1)mentioning
confidence: 61%
“…On the other hand, sequences of pathogenic taxa were also frequently found in other tannery wastewaters. Ricketsiella and Arcobacter genera are pathogens of arthropods and humans, respectively (Chowdhary et al 2017). In addition, Campylobacter is reported as ubiquitous in sewage and it was found that human and animal wastes from abattoirs and animal treatment plants are major sources (Stampi et al 1999).…”
Section: S1)mentioning
confidence: 99%